Sentuhan Kasih programme closes relationship with generations through social and community activities - Akmal Asyraf, Mior Azalian (2023)
MANONG, 10 March 2023 - A total of 25 Universiti Malaysia Pahang (UMP) students consisting of the Yayasan UMP Squad took advantage of their semester break by participating in the Sentuhan Kasih@Manong, Perak programme to support the elderly and strengthen the relationship between generations of people at the Pondok Ar-Ridzuan School (PPPAR) and the local community recently.Sentuhan Kasih programme closes relationship with generations through social and community activities